Sustained-release composition as well as preparation method and application thereof
By loading the sustained-release substance on hydrotalcite and dispersing it in hyaluronic acid or its salt, a sustained-release composition was prepared, which solved the problem of insufficient drug release time in the treatment of osteoarthritis, and achieved longer sustained-release effects and higher therapeutic compliance.
Patent Information
- Application Number
- CN202410886207.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to achieve long-term sustained release in the treatment of osteoarthritis, resulting in insufficient drug release time and frequent medication administration, which increases the patient's pain and infection risk.
A sustained release composition is prepared by loading the sustained release substance on hydrotalcite and dispersing it in hyaluronic acid or its salt to prolong the release time of the drug.
A longer-term sustained release effect was achieved, reducing the need for frequent drug administration, reducing the risk of joint infection, and improving patient compliance and treatment effects.
Smart Images

Figure CN119548639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sustained release, in particular to a sustained release composition using hydrotalcite and hyaluronic acid or its salt as sustained release agents. Background Art
[0002] Drug sustained release uses a certain material as a carrier to slowly release the drug in the body at a certain speed within the required time range according to the designed dose, so as to achieve a more effective treatment of the disease. Drug sustained release can prolong the treatment time of the drug and reduce the adverse effects of repeated administration on the body. In the field of drug research, especially in the field of osteoarthritis treatment, drug sustained release has important research value.
[0003] Osteoarthritis (OA) is a degenerative disease caused by degenerative damage to articular cartilage, reactive hyperplasia of joint margins and subchondral bone due to many factors such as aging, obesity, strain, trauma, congenital abnormalities of joints, and joint deformities. The incidence of OA is very high. It is estimated that the number of OA patients worldwide is as high as 355 million, and 80% of people over 65 years old have clinical evidence of OA. It is expected that the incidence of OA will continue to rise with the aging of the global population. The clinical symptoms of OA include joint pain, stiffness, limited mobility, and deformity. Among them, joint pain is the most typical symptom of OA patients and the main reason for patients to seek medical treatment. Chronic pain not only reduces the patient's ability to work, but may also cause severe anxiety and depression, and increase the incidence of cardiovascular events and all-cause mortality. On the other hand, degenerative damage to articular cartilage is the root cause of the progression of OA. When the articular cartilage is completely degraded and the joint space disappears and fuses, most patients will have to undergo total knee arthroplasty (TKA) to restore knee function. TKA is expensive and brings a huge financial burden to patients and their families. Therefore, relieving the pain of OA patients and slowing down the degeneration of articular cartilage in OA patients are the main goals of OA treatment.
[0004] Currently, the first-line drugs used clinically to relieve pain in OA patients are non-steroidal anti-inflammatory drugs (NSAIDs), which are divided into local NSAIDs and systemic NSAIDs. Systemic NSAIDs may cause a series of side effects such as gastrointestinal reactions, bleeding and cardiovascular accidents. Locally applied NSAIDs have the advantages of few side effects and high safety, but they have problems such as rapid degradation and easy induction of local toxic reactions and inflammatory reactions. For example, injecting NSAIDs directly into the patient's joint cavity will inevitably lead to problems such as too fast drug degradation and local high concentration of drug biological toxicity.
[0005] Hydrogels have good biocompatibility and excellent mechanical properties. Functional hydrogels made from them can make up for the shortcomings of the current common OA therapies, such as short drug action time and difficulty in achieving cartilage tissue regeneration. For example, hyaluronic acid (HA) is the main component of synovial fluid. HA in synovial fluid gives synovial fluid a high degree of viscoelasticity and lubrication, enabling it to absorb stress and reduce friction between tissues, thus protecting cartilage and reducing the rate of cartilage destruction; HA also exerts analgesic effects by reducing the excitability of nerve activity and reducing pain mediators such as prostaglandins and bradykinin. In addition, HA, as a drug carrier, reacts with other drugs to form compounds, which can exert sustained-release and targeting effects. At present, there have been clinical studies that have used HA as a supplementary treatment for NSAIDs and achieved good results. However, the sustained release effect of NSAIDs and HA combined is not ideal. HA in the joint cavity can be degraded through multiple metabolic pathways such as hyaluronidase and oxygen free radicals, and its degradation rate is relatively fast. It still needs to be administered intra-articularly once a week to achieve sustained therapeutic effects. Repeated invasive operations greatly reduce patients' treatment compliance and increase the risk of joint cavity infection. Therefore, combining the clinical first-line analgesic drugs NSAIDs and HA, reducing the degradation rate of the two, and prolonging the action time of the two has far-reaching clinical significance for relieving the pain symptoms of osteoarthritis patients, improving patient compliance, avoiding the risk of joint cavity infection, and delaying the progression of OA patients.
[0006] To this end, scholars have constructed a series of hydrogels as drug carriers to achieve sustained release of drugs. For example, Wang RL et al. used poloxamer P407 and hyaluronic acid as drug sustained-release hydrogels to sustain the release of diclofenac potassium, achieving a 4-day sustained-release effect (Andrographolide attenuates synovial inflammation ofosteoarthritis by inter⁃acting with tumor necrosis factor receptor 2trafficking in a rat model[J]. Journal of Orthopaedic Translation, 2021, 29:89-99.).
[0007] Japanese scholar Kenji Miyamoto proposed a hyaluronic acid derivative and its production method in which an anti-inflammatory compound is covalently bonded to hyaluronic acid through a spacer having a degradable part in the body. Specifically, a new derivative is obtained by chemically introducing NSAIDs or DMARD into sodium hyaluronate through a drug, and then injecting it into the affected part, which helps to relieve the pain associated with arthritis and fundamentally cure arthritis.
[0008] However, although the above methods slow down the release of anti-inflammatory drugs such as NSAIDs or DMARDs, their sustained release time does not exceed one week, which is far from meeting the clinical needs of long-term treatment of osteoarthritis, reduces patients' medical compliance, and increases the risk of infection.
[0009] Therefore, how to utilize hyaluronic acid to achieve a longer-lasting sustained-release effect for conditions including osteoarthritis remains a problem that needs to be solved urgently. Summary of the invention
[0010] Based on the problems existing in the prior art, the present invention provides a sustained-release composition, which uses hydrotalcite and hyaluronic acid or its salt as sustained-release agents, can effectively prolong the release time of the sustained-release substance, and play a more long-lasting sustained-release effect.
[0011] In order to achieve the above object, the present invention adopts the following technical solution: A sustained-release composition comprises a substance to be sustained-released, hydrotalcite as a sustained-release agent and hyaluronic acid or its salt, wherein the substance to be sustained-released is located on the hydrotalcite, and the hydrotalcite is dispersed on the hyaluronic acid or its salt.
[0012] Furthermore, the mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
[0013] A sustained-release composition comprises a substance to be sustained-released, hydrotalcite as a sustained-release agent, and hyaluronic acid or a salt thereof. The preparation method of the sustained-release composition comprises the following steps: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with the sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
[0014] Furthermore, in the step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours; in the step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours.
[0015] Furthermore, the mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
[0016] A method for preparing a sustained-release composition, the method comprising the following steps: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with the sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
[0017] Furthermore, in the step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours; in the step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours.
[0018] Furthermore, the mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
[0019] The sustained-release composition or the sustained-release composition prepared according to the preparation method is used in sustained-release products.
[0020] Use of the sustained-release composition or the sustained-release composition prepared according to the above preparation method in the preparation of medicines and / or medical device products.
[0021] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses a combination of hydrotalcite and hyaluronic acid or its salt as a sustained-release agent, which has a longer sustained-release effect than using hyaluronic acid or its salt alone as a sustained-release agent, or using a compound of hyaluronic acid or its salt as a sustained-release agent.
[0022] 2. Based on the above-mentioned sustained-release effect of the present invention, the sustained-release agent of the present invention can be applied not only to the treatment of osteoarthritis, but also to other systems requiring long-term slow release, providing a new solution and idea for the sustained-release system.
[0023] 3. The sustained-release agent of the present invention can utilize the beneficial effects of hyaluronic acid or its salts on the animal body, such as the analgesic effect on osteoarthritis, to improve the therapeutic effect.
[0024] 4. When used in the treatment of osteoarthritis, the sustained-release composition of the present invention can greatly reduce the pain caused by repeated intra-articular injections to osteoarthritis patients, reduce the risk of joint infection caused by repeated intra-articular injections, increase patients' compliance with medical treatment, and improve the prognosis of osteoarthritis patients.
[0025] 5. The preparation method of the sustained-release composition of the present invention is simple, the raw materials are widely available, the cost is low, and it is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the sustained-release composition prepared in Example 1; Figure 2 This is the SEM image of the sustained-release composition prepared in Example 7; Figure 3 This is the SEM image of the sustained-release composition prepared in Example 9; Figure 4The sustained-release test results of the sustained-release compositions prepared in Example 1 and Comparative Examples 1 and 2 are shown; Figure 5 The sustained-release test results of the sustained-release compositions prepared in Example 7 and Comparative Examples 3 and 4 are shown; Figure 6 The sustained-release test results of the sustained-release compositions prepared in Example 8 and Comparative Example 5 are shown; Figure 7 The sustained-release test results of the sustained-release composition prepared in Examples 1-3 are shown; Figure 8 The sustained-release test results of the sustained-release composition prepared in Examples 4-6 are shown; Fig. 9 The in vitro biosafety test results of the sustained-release compositions prepared in Example 1 and Example 7 are shown; Fig.10 The analgesic effect time chart of the sustained-release composition prepared in Example 1 and Example 7; Fig.11 This is a graph showing the in vivo biosafety test results of the sustained-release compositions prepared in Example 1 and Example 7. DETAILED DESCRIPTION
[0027] The present invention provides a sustained-release composition, comprising a substance to be sustained-released, hydrotalcite as a sustained-release agent, and hyaluronic acid or its salt, wherein the substance to be sustained-released is located on the hydrotalcite, and the hydrotalcite is dispersed on the hyaluronic acid or its salt.
[0028] The hydrotalcite (Layered double hydroxides, LDH), also known as layered composite hydroxide, is a type of two-dimensional nanomaterial composed of MO6 edge-sharing octahedral main layers and negatively charged interlayer anions. LDH has a large specific surface area and adjustable interlayer spacing, and is loaded by ion exchange, coprecipitation, physical adsorption and other methods.
[0029] In some embodiments of the present invention, the structural formula of the hydrotalcite is M 2+ 1-x M 3+ x (OH)2] x+ (A n- ) x / n mH2O; Among them, M 2+ is a divalent metal ion, which can be selected from Ca 2+ Mg 2+ 、Zn 2+ 、Ni 2+ , Mn 2+ 、Co 2+ , Fe 2+One, two or more of the above; M 3+ is a trivalent metal ion, which can be selected from Al 3+ Cr 3+ , Mn 3+ , Fe 3+ , Ga 3+ 、Co 3+ 、Ni 3+ One, two or more of the above; A n- is an inorganic anion, n is 1 or 2, and can be selected from OH - 、F - , Cl - Br - ,I - 、NO 3- 、CO3 2- 、SO4 2- One, two or more of the above; 0.2≤x≤0.8, can be selected from 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8; m is usually 0.5~4, and can be selected from 0.5, 1, 1.5, 2, 2.5, 3, 3.5, and 4.
[0030] In some preferred embodiments of the present invention, the M 2+ Mg 2+ .
[0031] In some preferred embodiments of the present invention, the M 3+ For Al 3+ .
[0032] In some preferred embodiments of the present invention, the A n- NO 3- 、CO3 2- , Cl - One, two or more of the above.
[0033] In some embodiments of the present invention, the hydrotalcite can be purchased from the market or prepared by itself. The self-preparation method is a common preparation method of hydrotalcite, including but not limited to coprecipitation method, ion exchange method, hydrothermal synthesis method, roasting recovery method, colloid mill method, ammonia method, etc. The present invention does not make specific restrictions, and those skilled in the art can make conventional selections as long as hydrotalcite can be obtained.
[0034] In some embodiments of the present invention, the hydrotalcite is prepared by a colloidal mill method, wherein the mixed solution of the above-mentioned divalent and trivalent metal ions is mixed with an alkaline solution, the pH is controlled to be about 9 to 11, and the mixture is dried to obtain the hydrotalcite. Taking aluminum-magnesium hydrotalcite as an example, the divalent metal ion may be a magnesium salt, and the trivalent metal ion may be an aluminum salt. For example, the magnesium salt, the aluminum salt and water are mixed to obtain a mixed solution, and then the mixed solution is mixed with an alkaline solution and dried to obtain the hydrotalcite. The magnesium salt includes but is not limited to one or more of magnesium nitrate, magnesium chloride and magnesium carbonate, and the aluminum salt includes but is not limited to one or more of aluminum nitrate, aluminum chloride and aluminum carbonate.
[0035] In the above-mentioned colloid mill method, the molar ratio of the divalent and trivalent metal ions can be (0.5-5):1, and the molar ratio of the divalent and trivalent metal ions can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc.
[0036] In some embodiments of the present invention, the concentration of the divalent metal ions in the mixed solution can be 0.1-0.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L.
[0037] In some embodiments of the present invention, the concentration of trivalent metal ions in the mixed solution can be 0.05-0.3 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L.
[0038] In some embodiments of the present invention, the concentration of the divalent metal ions in the mixed solution may be 0.2 to 0.4 mol / L.
[0039] In some embodiments of the present invention, the concentration of the trivalent metal ion may be 0.1 to 0.2 mol / L.
[0040] In the above-mentioned colloid mill method, those skilled in the art can select the type of the alkali solution from commonly used alkaline substances, such as sodium hydroxide, potassium hydroxide, etc. As for the concentration of the alkali solution and the volume ratio of the mixed solution to the alkali solution, as long as the pH of the solution after the mixed solution and the alkali solution are mixed is about 9 to 11, it can be used.
[0041] In some embodiments of the present invention, the OH in the alkali solution - The concentration is 0.1 to 1.5 mol / L. For example, OH -The concentration can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc., preferably 0.6-1.2 mol / L.
[0042] In some embodiments of the present invention, the volume ratio of the mixed liquid to the alkali solution can be 1:(0.1-5), for example, the volume ratio of the mixed liquid to the alkali solution can be 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.
[0043] In some embodiments of the present invention, the drying conditions are the drying conditions commonly used in the art, for example, it can be dried at 55-130°C for 10-60 h, and the drying temperature can specifically be 55°C, 60°C, 65°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or 130°C.
[0044] In some embodiments of the present invention, the drying time can be 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, or 60 h.
[0045] The hydrotalcite obtained by the colloid mill method may further include post-treatment steps commonly used in the art, such as centrifugal washing, which may be performed 1 to 10 times, specifically 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 times.
[0046] In some embodiments of the present invention, the centrifugal speed can be 1000-20000 r / min, such as 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, 6000 r / min, 7000 r / min, 8000 r / min, 9000 r / min, 10000 r / min, 11000 r / min, 12000 r / min, 13000 r / min, 14000 r / min, 15000 r / min, 16000 r / min, 17000 r / min, 18000 r / min, 19000 r / min, 20000 r / min. Each centrifugal time can be 1-10 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.
[0047] In some embodiments of the present invention, the hydrotalcite is prepared by an ammonia water method, and a mixed solution of divalent and trivalent metal ions is mixed with ammonia water, and the pH is controlled to be about 9 to 11 to obtain the hydrotalcite. Taking aluminum-magnesium hydrotalcite as an example, the divalent metal ion can be a magnesium salt, and the trivalent metal ion can be an aluminum salt. For example, the magnesium salt, the aluminum salt and water are mixed to obtain a mixed solution, and then the mixed solution is mixed with ammonia water, and the pH is controlled to be about 9 to 11 to obtain the hydrotalcite. The magnesium salt includes but is not limited to one or more of magnesium nitrate, magnesium chloride and magnesium carbonate, and the aluminum salt includes but is not limited to one or more of aluminum nitrate, aluminum chloride and aluminum carbonate.
[0048] In the above-mentioned ammonia method, the molar ratio of the divalent and trivalent metal ions can be (0.5-5):1. For example, the molar ratio of the divalent and trivalent metal ions can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc.
[0049] In some embodiments of the present invention, the concentration of divalent metal ions in the mixed solution may be 0.1 to 0.5 mol / L, such as 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L. In the mixed solution, the concentration of trivalent metal ions may be 0.05 to 0.3 mol / L, such as 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L. Preferably, the concentration of divalent metal ions in the mixed solution may be 0.2 to 0.4 mol / L, and the concentration of trivalent metal ions may be 0.1 to 0.2 mol / L.
[0050] In some embodiments of the present invention, the type of the alkali solution can be selected by those skilled in the art from commonly used alkaline substances, such as sodium hydroxide, potassium hydroxide, etc. The present application does not limit the concentration of the alkali solution and the volume ratio of the mixed solution to the alkali solution, as long as the pH of the solution after the mixed solution and the alkali solution are mixed is about 9 to 11.
[0051] In some embodiments of the present invention, the OH in the alkali solution - The concentration is 0.1 to 1.5 mol / L. For example, OH - The concentration can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc., preferably 0.6-1.2 mol / L.
[0052] The hydrotalcite obtained by the ammonia method may further include post-treatment steps commonly used in the art, such as centrifugal washing, the number of times may be 1 to 10 times, specifically 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times.
[0053] In some embodiments of the present invention, the centrifugal speed can be 1000-20000 r / min, for example 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, 6000 r / min, 7000 r / min, 8000 r / min, 9000 r / min, 10000 r / min, 11000 r / min, 12000 r / min, 13000 r / min, 14000 r / min, 15000 r / min, 16000 r / min, 17000 r / min, 18000 r / min, 19000 r / min, 20000 r / min.
[0054] In some embodiments of the present invention, the time of each centrifugation can be 1 to 10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.
[0055] The hyaluronic acid or its salt includes but is not limited to hyaluronic acid, sodium hyaluronate, potassium hyaluronate, zinc hyaluronate, calcium hyaluronate, magnesium hyaluronate, gold hyaluronate and the like.
[0056] In some embodiments of the present invention, the molecular weight of the hyaluronic acid or its salt is 1wDa to 300wDa, for example, 1wDa, 3wDa, 5wDa, 8wDa, 10wDa, 13wDa, 15wDa, 18wDa, 20wDa, 23wDa, 25wDa, 28wDa, 30wDa, 33wDa, 35wDa, 38wDa, 40wDa, 43wDa, 45wDa, 48wDa, 50wDa, 53wDa, 55wDa, 58wDa, 60wDa, 63wDa, 65wDa, 68wDa, 70wDa, 73wDa, 75wDa, 78wDa, 80wDa, 83wDa, 84wDa, 85wDa, 86wDa, 87wDa, 88wDa, 89wDa, 90wDa, 91wDa, 92wDa, 93wDa, 94wDa, 95wDa, 96wDa, 97wDa, 98wDa, 99wDa, 100wDa, 101wDa, 102wDa, 103wDa, 104wDa any value among 5wDa, 88wDa, 90wDa, 93wDa, 95wDa, 98wDa, 100wDa, 110wDa, 120wDa, 130wDa, 140wDa, 150wDa, 160wDa, 170wDa, 180wDa, 190wDa, 200wDa, 210wDa, 220wDa, 230wDa, 240wDa, 250wDa, 260wDa, 270wDa, 280wDa, 290wDa, and 300wDa, or any range therebetween, and the molecular weight is the weight average molecular weight.
[0057] When hydrotalcite and hyaluronic acid or its salt are used in combination, the two are stirred and mixed in an aqueous environment to form a structure in which the hydrotalcite is dispersed on the hyaluronic acid or its salt.
[0058] In some embodiments of the present invention, the mass ratio of the hydrotalcite, hyaluronic acid or its salt is 1:(0.2-5), specifically, it can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, preferably 1:(0.5-2).
[0059] In some embodiments of the present invention, the substance to be released is bound to the hydrotalcite (inside and / or on the surface) by physical effects (such as electrostatic effects, van der Waals forces, etc.).
[0060] In some embodiments of the present invention, the loading rate of the hydrotalcite to the sustained-released substance may be 10% to 80%, wherein the loading rate = the mass of the sustained-released substance / (the mass of the sustained-released substance + the mass of the hydrotalcite) × 100%. In some embodiments of the present invention, the loading rate is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%.
[0061] In some embodiments of the present invention, the mass ratio of the hydrotalcite to the sustained-release substance is 1:(0.2-5), specifically, it can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, preferably 1:(0.5-2).
[0062] In some embodiments of the present invention, the sustained-release substance may be a drug component or a non-drug component. The sustained-release substance is preferably a water-soluble component.
[0063] In some embodiments of the present invention, the drug ingredients include, but are not limited to, anti-inflammatory drugs, anesthetic drugs, neurological drugs, psychiatric drugs, anti-tumor drugs, cardiovascular drugs, respiratory drugs, digestive drugs, urinary system drugs, analgesic drugs, or other drugs that require long-term slow release. Those skilled in the art can make a selection according to the specific indications, and the type of drug does not affect the long-term slow release effect of the sustained-release composition. For example, for the treatment of osteoarthritis, non-steroidal anti-inflammatory drugs can be selected, and the non-steroidal anti-inflammatory drugs include one, two or more of meloxicam, diclofenac, salicylic acid, aspirin, mefenamic acid, tolfenamic acid, flufenamic acid, sulindac, fenbutic acid, indomethacin, acemetacin, amfenac, etodolac, felbinac, ibuprofen, flurbiprofen, ketoprofen, naproxen, pranoprofen, fenoprofen, tiaprofenic acid, oxaprozin, loxoprofen, alminoprofen, zaltoprofen, piroxicam, tenoxicam, lornoxicam, meloxicam, thiamide, tolmetin, diflunisal, acetaminophen, fluquinoxalate, tenoridine and actarik.
[0064] In some embodiments of the present invention, the non-drug ingredients include, but are not limited to, ingredients beneficial to the skin, diagnostic markers, or other non-drug ingredients that require long-term slow release.
[0065] In some preferred embodiments of the present invention, the sustained-release substance is a non-steroidal anti-inflammatory drug.
[0066] In some embodiments of the present invention, the sustained-release composition further comprises other ingredients, such as a dispersant, a solvent, a pH regulator, an osmotic pressure regulator, and the like.
[0067] In some specific embodiments, the solvent comprises water.
[0068] In some specific embodiments, the dispersant includes one or two of polyethylene glycol, polyvinyl pyrrolidone, and bovine serum albumin.
[0069] The present application provides a sustained-release composition, comprising a sustained-release substance, hydrotalcite as a sustained-release agent, and hyaluronic acid or a salt thereof. The preparation method of the sustained-release composition comprises the following steps: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with the sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
[0070] In some embodiments of the present invention, in step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours, for example, 20 hours, 24 hours, 30 hours, 36 hours, 40 hours, 45 hours, 48 hours, or 50 hours.
[0071] In some embodiments of the present invention, in step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours, for example, 20 hours, 24 hours, 30 hours, 36 hours, 40 hours, 45 hours, 48 hours, or 50 hours.
[0072] In some embodiments of the present invention, the mass ratio of hydrotalcite, supported substance, and hyaluronic acid or its salt in step a and step b is 1:(0.2-5):(0.2-5), preferably 1:(0.5-2):(0.5-2).
[0073] In some embodiments of the present invention, the mass ratio of hydrotalcite to the sustained-release substance in step a is 1:(0.2-5), preferably 1:(0.5-2).
[0074] In some embodiments of the present invention, the mass ratio of hydrotalcite, hyaluronic acid or its salt in step a and step b is 1:(0.2-5), preferably 1:(0.5-2).
[0075] In some embodiments of the present invention, in step a, the concentration of hydrotalcite is 1-10 mg / mL, for example, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, and the concentration of the sustained-release substance is 5-20 mg / mL, for example, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL.
[0076] In some embodiments of the present invention, in step b, the concentration of hyaluronic acid or its salt is 5-20 mg / mL, for example 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL.
[0077] The present invention also provides a method for preparing a sustained-release composition, comprising the following steps: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with a sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
[0078] In some embodiments of the present invention, in step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours, for example, 20 hours, 24 hours, 30 hours, 36 hours, 40 hours, 45 hours, 48 hours, or 50 hours.
[0079] In some embodiments of the present invention, in step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours, for example, 20 hours, 24 hours, 30 hours, 36 hours, 40 hours, 45 hours, 48 hours, or 50 hours.
[0080] In some embodiments of the present invention, the mass ratio of hydrotalcite, sustained-release substance, and hyaluronic acid or its salt in step a and step b is 1:(0.2-5):(0.2-5), preferably 1:(0.5-2):(0.5-2).
[0081] In some embodiments of the present invention, the mass ratio of hydrotalcite to the sustained-release substance in step a is 1:(0.2-5), preferably 1:(0.5-2).
[0082] In some embodiments of the present invention, the mass ratio of hydrotalcite, hyaluronic acid or its salt in step a and step b is 1:(0.2-5), preferably 1:(0.5-2).
[0083] In some embodiments of the present invention, in step a, the concentration of hydrotalcite is 1-10 mg / mL, for example, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, and the concentration of the sustained-release substance is 5-20 mg / mL, for example, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL.
[0084] In some embodiments of the present invention, in step b, the concentration of hyaluronic acid or its salt is 5-20 mg / mL, for example 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL.
[0085] In some specific embodiments, the method for preparing the above-mentioned sustained-release composition comprises the following steps: a. The hydrotalcite and the sustained-release substance are mixed in a water solvent, and a dispersant is added to mix to obtain a hydrotalcite loaded with a sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in a water solvent to obtain the composition.
[0086] In some more specific embodiments, in step a, the sustained-release substance is first mixed with water, and after the sustained-release substance is completely dissolved, hydrotalcite is added for a first mixing, and after mixing, centrifugal washing is performed, and water is added to the original water content. Then, a dispersant is added for a second mixing, and after mixing, centrifugal washing is performed, and water is added to the original water content.
[0087] In some embodiments of the present invention, the dispersant includes one or two of polyethylene glycol, polyvinyl pyrrolidone, and bovine serum albumin. The function of the dispersant is to make the substance disperse more evenly.
[0088] In some embodiments of the present invention, the weight average molecular weight of the dispersant is 1500-2500, specifically 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, etc.
[0089] In some embodiments of the present invention, the concentration of hydrotalcite in step a is 1-10 mg / mL, and the concentration of the sustained-release substance is 5-20 mg / mL; the concentration of hyaluronic acid or its salt in step b is 5-20 mg / mL.
[0090] In some embodiments of the present invention, in step a, the first mixing time is 20 to 50 h, and the second mixing time is 20 to 50 h; in step b, the mixing time is 20 to 50 h.
[0091] In some embodiments of the present invention, the rotation speed of the centrifugal water washing can independently be 5000-15000 r / min, specifically 5000 r / min, 5500 r / min, 6000 r / min, 6500 r / min, 7000 r / min, 7500 r / min, 8000 r / min, 8200 r / min, 8500 r / min, 8800 r / min, 9000 r / min, 9200 r / min, 9500 r / min, 9800 r / min, 10000 r / min, 11000 r / min, 12000 r / min, 13000 r / min, 14000 r / min, 15000 r / min and the like.
[0092] In some embodiments of the present invention, the centrifugal washing time can independently be 1 to 5 min, specifically 1.0 min, 1.5 min, 2.0 min, 2.2 min, 2.2 min, 2.5 min, 2.8 min, 3 min, 3.2 min, 3.5min, 3.8 min, 4.0 min, 4.5 min, 5.0 min, etc.
[0093] In some embodiments of the present invention, the mixing includes stirring and mixing.
[0094] In some embodiments of the present invention, the mass ratio of hydrotalcite, sustained-release substance, and hyaluronic acid or its salt in step a and step b is 1:(0.2-5):(0.2-5), preferably 1:(0.5-2):(0.5-2).
[0095] In some embodiments of the present invention, the mass ratio of hydrotalcite to the sustained-release substance in step a is 1:(0.2-5), preferably 1:(0.5-2).
[0096] In some embodiments of the present invention, the mass ratio of hydrotalcite to dispersant in step a is 1:(5-10), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10.
[0097] In some embodiments of the present invention, the mass ratio of hydrotalcite, hyaluronic acid or its salt in step a and step b is 1:(0.2-5), preferably 1:(0.5-2).
[0098] The present invention also provides use of the sustained-release composition in sustained-release products.
[0099] In some embodiments of the present invention, the sustained-release product includes an injection solution, a lyophilized powder, and the like.
[0100] The present invention also provides use of the sustained-release composition in preparing medicines and / or medical device products.
[0101] In some embodiments of the present invention, when the sustained-release substance is a non-steroidal anti-inflammatory drug, the sustained-release composition of the present invention can be used for intra-articular injection.
[0102] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0103] Preparation of LDH: Preparation Example 1 Add a certain amount of magnesium nitrate and aluminum nitrate to a beaker, add 200 mL of distilled water to dissolve, and obtain a mixed solution, so that the concentrations of magnesium salt and aluminum salt are 0.2 mol / L and 0.1 mol / L respectively. Add sodium hydroxide to another beaker, add a certain amount of distilled water to dissolve, and make the concentration of sodium hydroxide 0.6 mol / L. Pour the mixed solution and sodium hydroxide solution into a colloid grinding machine and mix evenly (pH=9-11); dry at 80℃ for 24 h; wash with deionized water, centrifuge three times (speed is 10000 r / min, 3 min each time), and disperse with appropriate amount of water to obtain LDH. Preparation Example 2 Add a certain amount of magnesium chloride and aluminum nitrate to a beaker, add 200mL of distilled water to dissolve, and obtain a mixed solution, so that the concentrations of magnesium salt and aluminum salt are 0.3 mol / L and 0.15 mol / L respectively. Add sodium hydroxide to another beaker, add a certain amount of distilled water to dissolve, and make the concentration of sodium hydroxide 0.9 mol / L. Pour the mixed solution and sodium hydroxide solution into a colloid grinding machine and mix evenly (pH=9-11); dry at 100℃ for 24 hours; wash with deionized water, centrifuge three times (speed is 9000 r / min, 3 min each time), and disperse with appropriate amount of water to obtain LDH. Preparation Example 3 Add a certain amount of magnesium chloride and aluminum nitrate to a beaker, add 200 mL of distilled water to dissolve, and obtain a mixed solution, so that the concentrations of magnesium salt and aluminum salt are 0.4 mol / L and 0.2 mol / L respectively. Add sodium hydroxide to another beaker, add a certain amount of distilled water to dissolve, and make the concentration of sodium hydroxide 1.2 mol / L. Pour the mixed solution and sodium hydroxide solution into a colloid grinding machine and mix evenly (pH=9-11); dry at 120℃ for 12 h; wash with deionized water, centrifuge three times (speed is 8000 r / min, 3 min each time), and disperse with appropriate amount of water to obtain LDH. Preparation Example 4 Add a certain amount of magnesium nitrate and aluminum chloride to a beaker, add 200 mL of distilled water to dissolve, and obtain a mixed solution, so that the concentrations of magnesium salt and aluminum salt are 0.3 mol / L and 0.1 mol / L respectively. Add sodium hydroxide to another beaker, add a certain amount of distilled water to dissolve, and make the concentration of sodium hydroxide 0.6 mol / L. Pour the mixed solution and sodium hydroxide solution into a colloid grinding machine and mix evenly (pH=9-11); dry at 80℃ for 48 h; wash with deionized water, centrifuge four times (speed is 9000 r / min, 3 min each time), and disperse with appropriate amount of water to obtain LDH. Preparation Example 5 Add a certain amount of magnesium nitrate and aluminum nitrate to a beaker, add 200-400 mL of distilled water to dissolve them so that the concentrations of magnesium salt and aluminum salt are 0.3 mol / L and 0.15 mol / L, respectively, and quickly drop ammonia water into it. Use a pH meter to detect and control the pH to around 9-11. Stop adding ammonia water, stir at room temperature for about 30 minutes, wash with ethanol and deionized water respectively, centrifuge three times (speed is 9000 r / min, 3 min each time), disperse with appropriate amount of water to obtain LDH.
[0104] Preparation of sustained release composition: Example 1 (LDH / ML / HA=1:1:1, HA 130w, LDH obtained in Preparation Example 1) Step a: Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve, and then add 200 mg of LDH (LDH 10 mg / mL) obtained in Preparation Example 1, wherein the mass ratio of LDH to ML is 1:1. Stir for 48 hours, centrifuge and wash twice, and add to the original water content to obtain a hydrotalcite dispersion loaded with ML.
[0105] Step b: Take the hydrotalcite dispersion loaded with ML prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: ML: hyaluronic acid is about 1:1:1, stir at a speed of 1300r / min for 24 h and then package to obtain a sustained-release composition loaded with ML.
[0106] Example 2 (LDH / ML / HA=1:1:0.5, HA 130w, LDH obtained in Preparation Example 1) The operation is the same as that of Example 1, except that in step b, the amount of sodium hyaluronate with a molecular weight of 130w Da added is 100 mg (5 mg / mL), wherein the mass ratio of hydrotalcite: ML: hyaluronic acid is about 1:1:0.5.
[0107] Example 3 (LDH / ML / HA=0.5:1:1, HA 130w, LDH obtained in Preparation Example 1) Step a: Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve, and then add 100 mg of LDH (LDH 5 mg / mL) obtained in Preparation Example 1, wherein the mass ratio of LDH to ML is 0.5:1. Stir for 48 hours, centrifuge and wash twice, and add to the original water content to obtain a hydrotalcite dispersion loaded with ML.
[0108] Step b: Take the hydrotalcite dispersion loaded with ML prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: ML: hyaluronic acid is about 0.5:1:1, stir at a speed of 1300r / min for 24 h and then package to obtain a sustained-release composition loaded with ML.
[0109] Example 4 (LDH / ML / HA=1:1:1, HA 30w, LDH obtained in Preparation Example 1) The operation is the same as that of Example 1, except that in step b, the molecular weight of sodium hyaluronate is 30w Da.
[0110] Example 5 (LDH / ML / HA=1:1:1, HA 70w, LDH obtained in Preparation Example 1) The operation is the same as that of Example 1, except that in step b, the molecular weight of sodium hyaluronate is 70w Da.
[0111] Example 6 (LDH / ML / HA=1:1:1, HA230w, LDH obtained in Preparation Example 1) The operation is the same as that of Example 1, except that in step b, the molecular weight of sodium hyaluronate is 230w Da.
[0112] Example 7 (LDH / DS / HA=1:1:1, HA 130w, LDH obtained in Preparation Example 4, colloid milling method) Step a: Weigh 200 mg of diclofenac (DS), add a certain amount of water (diclofenac 10 mg / mL) to completely dissolve, and then add 200 mg of LDH obtained in Preparation Example 4 (LDH 10 mg / mL), wherein the mass ratio of LDH to DS is 1:1. Stir for 45 h, centrifuge and wash twice, and add to the original water content to obtain a hydrotalcite dispersion loaded with DS.
[0113] Step b: Take the DS-loaded hydrotalcite dispersion prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: DS: hyaluronic acid is about 1:1:1, stir at a speed of 1300 r / min for 24 h and then package to obtain a DS-loaded sustained-release composition.
[0114] Example 8 (LDH / DS / HA=1:1:1, HA 130w, LDH obtained in Preparation Example 5, ammonia method) Step a: Weigh 200 mg of diclofenac (DS), add a certain amount of water (diclofenac 10 mg / mL) to completely dissolve, and then add 200 mg of LDH obtained in Preparation Example 5 (LDH 10 mg / mL), wherein the mass ratio of LDH to DS is 1:1. Stir for 45 h, centrifuge and wash twice, and add to the original water content to obtain a hydrotalcite dispersion loaded with DS.
[0115] Step b: Take the DS-loaded hydrotalcite dispersion prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: DS: hyaluronic acid is about 1:1:1, stir at a speed of 1300 r / min for 24 h and then package to obtain a DS-loaded sustained-release composition.
[0116] Example 9 (LDH / ML / HA=1:1:1, HA 130w, LDH obtained in Preparation Example 2) Step a: Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve, then add 200 mg of LDH obtained in Preparation Example 2 (LDH 10 mg / mL), where the mass ratio of LDH to ML is 1:1. Stir for 36 hours, centrifuge and wash twice, and replenish to the original water content. Add 1.5 g of polyethylene glycol 2000, stir for 36 hours, centrifuge and wash once (speed is 9000 r / min, 3 min each time), add a certain amount of water to filter (10 μm filter membrane), centrifuge at 1000 r / min after complete filtration, replenish to the original water content, and obtain a hydrotalcite dispersion loaded with ML.
[0117] Step b: Take the hydrotalcite dispersion loaded with ML prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: ML: hyaluronic acid is about 1:1:1, stir at a speed of 1200 r / min for 36 h and then package to obtain a sustained-release composition loaded with ML.
[0118] Example 10 (LDH / ML / HA=1:1:1, HA 130w, LDH obtained in Preparation Example 3) Step a: Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve, then add 200 mg of LDH obtained in Preparation Example 3 (LDH 10 mg / mL), where the mass ratio of LDH to ML is 1:1. Stir for 24 hours, centrifuge and wash twice, and replenish to the original water content. Add 1.2 g of polyethylene glycol 2000, stir for 24 hours, centrifuge and wash once (speed is 8000 r / min, 3 min each time), add a certain amount of water to filter (10 μm filter membrane), centrifuge at 1000 r / min after complete filtration, replenish to the original water content, and obtain a hydrotalcite dispersion loaded with ML.
[0119] Step b: Take the hydrotalcite dispersion loaded with ML prepared in step a, add 200 mg (10 mg / mL) of sodium hyaluronate with a molecular weight of 130w Da, wherein the mass ratio of hydrotalcite: ML: hyaluronic acid is about 1:1:1, stir at a speed of 1500r / min for 24 h and then package to obtain a sustained-release composition loaded with ML.
[0120] Comparative Example 1 (ML:HA=1:1, the only difference from Example 1 is that LDH is not added) Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve it, then add 200 mg of sodium hyaluronate with a molecular weight of 130w Da, where the mass ratio of ML: hyaluronic acid is about 1:1. Stir at a speed of 1300 r / min for 24 h and then package to obtain a sustained-release composition loaded with ML.
[0121] Comparative Example 2 (LDH:ML=1:1, the only difference from Example 1 is that HA is not added) Weigh 200 mg of meloxicam (ML), add a certain amount of water (meloxicam 10 mg / mL) to completely dissolve, then add 200 mg of LDH (LDH 10 mg / mL) obtained in Preparation Example 1, where the mass ratio of LDH to ML is 1:1. Stir for 48 h, centrifuge and wash twice, add to the original water content, stir at a speed of 1300 r / min for 24 h, and then package to obtain a sustained-release composition loaded with ML.
[0122] Comparative Example 3 (DS:HA=1:1, the only difference from Example 7 is that LDH is not added) Weigh 200 mg of diclofenac (DS), add a certain amount of water (diclofenac 10 mg / mL) to completely dissolve it, then add 200 mg of sodium hyaluronate with a molecular weight of 130w Da, where the mass ratio of DS: hyaluronic acid is about 1:1. Stir at a speed of 1300 r / min for 24 h and then package to obtain a sustained-release composition loaded with DS.
[0123] Comparative Example 4 (LDH:DS=1:1, the only difference from Example 7 is that HA is not added) Weigh 200 mg of diclofenac (DS), add a certain amount of water (diclofenac 10 mg / mL) to completely dissolve, then add 200 mg of LDH obtained in Preparation Example 4 (LDH 10 mg / mL), where the mass ratio of LDH to DS is 1:1. Stir for 45 h, centrifuge and wash twice, add to the original water content, stir at a speed of 1300 r / min for 24 h, and then package to obtain a sustained-release composition loaded with DS.
[0124] Comparative Example 5 (DS:LDH=1:1, the only difference from Example 8 is that HA is not added) Weigh 200 mg of diclofenac (DS), add a certain amount of water (diclofenac 10 mg / mL) to completely dissolve, then add 200 mg of LDH obtained in Preparation Example 5 (LDH 10 mg / mL), where the mass ratio of LDH to DS is 1:1. Stir for 45 h, centrifuge and wash twice, add to the original water content, stir at a speed of 1300 r / min for 24 h, and then package to obtain a sustained-release composition loaded with DS.
[0125] Experimental Example 1 Structural Identification A small amount of the samples obtained in Example 1, Example 7, and Example 9 were placed on the conductive glue on the sample stage, and after gold spraying, the morphology of the samples was observed using a Zeiss SUPRA 55 field emission scanning electron microscope (FESEM, Zeiss, Germany) at an accelerating voltage of 10 kV. The results are shown in FIG. Figure 1-3 shown.
[0126] Figure 1-3 In the figure, the left picture shows an electron microscope picture magnified to 200nm, and the right picture shows an electron microscope picture magnified to 1um. It can be seen from the part surrounded by the red dotted circle that the nano-scale LDH is dispersed on the micro-scale hyaluronic acid or its salt.
[0127] Experimental Example 2 Sustained Release Effect Detection (1) Investigation of the sustained-release effect of the combination of LDH and HA 2 mL of the sustained-release composition prepared in Example 1, Example 7, Example 8, and Comparative Examples 1-5 were placed in a dialysis bag with a cutoff of 3000, and the dialysis bag was placed in a centrifuge tube filled with 10 mL of PBS. The centrifuge tube was placed on a shaker and slowly shaken for 8 hours a day at a speed of 100 rpm, and the ambient temperature was maintained at 37° C. Samples were taken once a day with a sample volume of 10 mL, and fresh PBS was supplemented, and the sampling was continued for 90 days.
[0128] Weigh different weights of meloxicam (ML) or diclofenac (DS) standard samples to prepare standard sample solutions with different concentration gradients. Use an enzyme-labeled instrument to measure the absorbance of each ML standard sample at 362 nm and each DS standard sample at 290 nm, and draw an absorbance-sample mass standard curve. Use an enzyme-labeled instrument to measure the absorbance of each ML sample at 362 nm and each DS sample at 290 nm, and convert the mass of meloxicam (ML) or diclofenac (DS) corresponding to each sample according to the standard curve. The test results are as follows: Figure 4-6 shown.
[0129] pass Figure 4 It can be seen that in Comparative Example 1 (curve formed by red dots), when only sodium hyaluronate is used as a sustained-release agent, the sustained-release time of meloxicam (ML) is about 10 days, and in Comparative Example 2 (curve formed by blue squares), when only LDH is used as a sustained-release agent, the sustained-release time of meloxicam (ML) is less than 30 days. In Example 1 (curve formed by green triangles), when sodium hyaluronate and LDH are combined as sustained-release agents, the sustained-release time of meloxicam (ML) is about 60 days, and the sustained-release effect is much better than that of sodium hyaluronate alone as a sustained-release agent or LDH alone as a sustained-release agent, which indicates that the combination of sodium hyaluronate and LDH produces a synergistic sustained-release effect.
[0130] pass Figure 5 It can be seen that in Comparative Example 3 (curve formed by red dots), when only sodium hyaluronate is used as a sustained-release agent, the sustained-release time of diclofenac (DS) is about 30 days, and in Comparative Example 4 (curve formed by blue squares), when only LDH is used as a sustained-release agent, the sustained-release time of diclofenac (DS) is about 40 days. In Example 7 (curve formed by green triangles), when sodium hyaluronate and LDH are combined as sustained-release agents, the sustained-release time of diclofenac (DS) is about 75 days, and the sustained-release effect is much better than that of sodium hyaluronate alone as a sustained-release agent or LDH alone as a sustained-release agent, which indicates that the combination of sodium hyaluronate and LDH produces a synergistic sustained-release effect.
[0131] pass Figure 6 It can be seen that in Comparative Example 5 (the curve formed by the red squares) when only LDH is used as a sustained-release agent, the sustained-release time of diclofenac (DS) is about 40 days, while in Example 8 (the curve formed by the green triangles) when sodium hyaluronate and LDH are combined as sustained-release agents, the sustained-release time of diclofenac (DS) is about 70 days, and its sustained-release effect is far better than that of LDH alone as a sustained-release agent.
[0132] (2) Investigation of the sustained release effect of different mass ratios of LDH and HA 2 mL of the sustained-release composition prepared in Examples 1-3 was placed in a dialysis bag with a cutoff of 3000, and the dialysis bag was placed in a centrifuge tube containing 10 mL of PBS. The centrifuge tube was placed on a shaker and slowly shaken for 8 hours a day at a speed of 100 rpm, and the ambient temperature was maintained at 37°C. Samples were taken once a day with a sample volume of 10 mL, and fresh PBS was supplemented for 90 consecutive days. The absorbance of each sample at 362 nm was measured using an ELISA instrument, and the meloxicam (ML) corresponding to each sample was converted according to the standard curve.
[0133] The test results are as follows Figure 7 As shown, through Figure 7 It can be seen that the sustained-release compositions with a mass ratio of LDH to sodium hyaluronate in the range of 1: (0.5-2) all have an obvious sustained-release effect on meloxicam, and the in vitro sustained-release time of meloxicam is more than 40 days.
[0134] (3) Investigation of sustained-release effects of HA with different molecular weights as sustained-release test materials 2 mL of the sustained-release composition prepared in Examples 4-6 was placed in a dialysis bag with a cutoff of 3000, and the dialysis bag was placed in a centrifuge tube containing 10 mL of PBS. The centrifuge tube was placed on a shaker and slowly shaken for 8 h per day at a speed of 100 rpm, and the ambient temperature was maintained at 37°C. Samples were taken once a day with a sample volume of 10 mL, and fresh PBS was supplemented for 90 consecutive days. The absorbance of each sample at 362 nm was measured using an ELISA instrument, and the meloxicam (ML) corresponding to each sample was converted according to the standard curve.
[0135] The experimental results are as follows Figure 8 As shown, through Figure 8 It can be seen that the sustained-release compositions prepared using sodium hyaluronate with different molecular weights all have obvious sustained-release effects on meloxicam, and the in vitro sustained-release time of meloxicam is more than 40 days.
[0136] Experimental Example 3 In vitro biosafety test The experiment was divided into four groups, namely the Control group (C), the sodium hyaluronate group with a molecular weight of 130wDa (HA), the sustained-release composition group loaded with ML in Example 1 (ML), and the sustained-release composition group loaded with DS in Example 7 (DS). A cell suspension of human chondrocytes (100 μL / well) was added to a 96-well plate, and then 100 μL of sample was added to each well of each group, among which pure water was added to the Control group, and each group had three replicate wells. The culture plates were placed in an incubator and cultured for 1 day, 3 days, 5 days, and 7 days (37°C, 5% CO2). On the 1st, 3rd, 5th, and 7th day, the corresponding 96-well plates were taken out, 10 μL of CCK-8 solution was added to each well, and the culture plates were incubated in the incubator for 2 hours. The absorbance of each well at 362 nm (ML) and 290 nm (DS) was measured with an enzyme reader, and the data were recorded for subsequent statistical analysis. The analysis results are shown in the figure. Fig. 9 As shown. Fig. 9 It can be seen that the sustained-release compositions prepared in Example 1 and Example 7 have good biocompatibility with human chondrocytes.
[0137] Experimental Example 4 In vivo effectiveness and safety testing The experiment was conducted with 8-week-old male Wistar rats purchased from the Union Medical College Animal Center.
[0138] Before modeling, each rat was measured for weight bearing on both feet using a rat bipedal balance measuring instrument, and the ratio of right foot / left foot was used as the bipedal balance value. After the bipedal balance value was measured, grouping modeling and intervention began. Six groups were set up: ①Control group (blank control group) (8 rats); ②OA group (modeling group) (8 rats); ③OA+HA / ML (sustained-release composition prepared in comparative example 1) (8 rats); ④OA+HA / DS (sustained-release composition prepared in comparative example 3) (8 rats); ⑤OA+HA / LDH / ML (sustained-release composition prepared in Example 1) (8 rats); ⑥OA+ HA / LDH / DS (sustained-release composition prepared in Example 7) (8 rats). Except for the blank control group, rats in the other groups were modeled (50 μL of 20 mg / ml sterile sodium iodoacetate was injected into the right lower limb joint cavity, and 50 μL of PBS was injected into the right lower limb joint cavity of rats in the control group. After the model was successfully established, intra-articular administration and rat pain threshold detection were performed. On day 0, the bipedal balance values of all rats after modeling were measured. After the model was successfully established, 50 μL of the corresponding sustained-release composition was injected into the right lower limbs of rats in groups ③, ④, ⑤, and ⑥. The drug concentration in the sustained-release composition was 10 mg / ml. The bipedal balance values of all rats were measured on the 1st, 7th, 14th, 21st, 28th, and 35th days after administration. The heart, liver, spleen, lung, and kidney of rats on the 1st and 28th days after modeling were taken for pathological sections.
[0139] The bipedal balance values of rats in each group are as follows Fig.10 As shown in the figure, the bipedal balance value is higher than that of the OA group, which means that the sustained-release composition has an analgesic effect in rats. It can be seen from the figure that after the injection of the sustained-release composition of Comparative Example 1 (OA+HA / ML) and Comparative Example 3 (OA+HA / DS), the rats have a good analgesic effect on the same day, but the analgesic effect disappears after the 7th day. The analgesic effect in the rats injected with the sustained-release composition of Example 1 (OA+HA / LDH / ML) and Example 7 (OA+HA / LDH / DS) can last for 35 days, showing a good long-lasting sustained-release effect.
[0140] Rat heart, liver, spleen, lung and kidney pathological sections Fig.11 As shown in the figure, it can be seen that the sustained-release composition prepared in the present application has good biological safety in vivo.
[0141] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0142] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A sustained-release composition, characterized in that: The invention comprises a substance to be slowly released, hydrotalcite as a slow-release agent and hyaluronic acid or its salt. The substance to be slowly released is located on the hydrotalcite, and the hydrotalcite is dispersed on the hyaluronic acid or its salt.
2. The sustained-release composition according to claim 1, characterized in that The mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
3. A sustained-release composition, characterized in that: The sustained-release composition comprises a substance to be sustained-released, hydrotalcite as a sustained-release agent, and hyaluronic acid or a salt thereof. The preparation method of the sustained-release composition comprises the following steps: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with the sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
4. The sustained-release composition according to claim 3, characterized in that In the step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours; in the step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours.
5. The sustained-release composition according to claim 3 or 4, characterized in that: The mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
6. A method for preparing a sustained-release composition, characterized in that: The following steps are involved: a. The hydrotalcite and the sustained-release substance are mixed in water to obtain a hydrotalcite loaded with the sustained-release substance; b. The hydrotalcite loaded with the sustained-release substance obtained in step a is mixed with hyaluronic acid or a salt thereof in water to obtain the sustained-release composition.
7. The preparation method according to claim 6, characterized in that: In the step a, the mixing time of the hydrotalcite and the sustained-release substance is 20 to 50 hours; in the step b, the mixing time of the hydrotalcite loaded with the sustained-release substance and the hyaluronic acid or its salt is 20 to 50 hours.
8. The preparation method according to claim 6 or 7, characterized in that: The mass ratio of the hydrotalcite to hyaluronic acid or its salt is 1:(0.2-5).
9. Use of the sustained-release composition according to any one of claims 1 to 5 or the sustained-release composition prepared by the preparation method according to any one of claims 6 to 8 in sustained-release products.
10. Use of the sustained-release composition according to any one of claims 1 to 5 or the sustained-release composition prepared by the preparation method according to any one of claims 6 to 8 in the preparation of medicines and / or medical device products.